Metal Catalysed Reactions in Ionic Liquids - Dyson, Paul J.; Geldbach, Tilmann J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
Metal Catalysed Reactions in Ionic Liquids by Paul J. Dyson and Tilmann J. Geldbach Metal Catalysed Reactions in Ionic Liquids is the first non-edited book on the subject of metal catalysed reactions in ionic liquids and covers the literature from its origins until early 2005. The book begins with a general introduction to the field of biphasic/multiphasic catalysis and describes the synthesis, functionalisation and fundamental properties of ionic liquids relevant to catalysis. In the following chapters catalysed reactions are discussed according to their type, including: hydrogenation hydroformylation oxidation C-C coupling reactions metathesis dimerisation polymerisation Trends, generalisations, advantages and disadvantages of ionic liquids for specific reaction types are discussed. In addition, specific processes such as supported ionic liquid phase catalysis, continuous processes using CO2 extraction and nanoparticle catalysis are covered. This book is an invaluable resource for all those working in catalysis, green chemistry, and advanced synthetic methods, especially advanced level undergraduate and graduate students and those researching or contemplating research in biphasic or multiphasic catalysis using ionic liquids. .
Ionic Liquids-Properties and Preparation -- Hydrogenation -- Hydroformylation -- Oxidation Reactions -- Carbon-Carbon Coupling Reactions -- Olefin Metathesis -- Dimerisation-Polymerisation -- Miscellaneous Reactions.
Keywords: Inorganic chemistry; Organic chemistry; Catalysis; Inorganic Chemistry; Organic Chemistry; Catalysis